Pencemaran Laut oleh Limbah Batu Bara di Aceh Barat dalam Perspektif Hukum Laut terhadap Keberlanjutan Perikanan - Annisa Putri Valliandry; Azzahra Rahma Adila Putri; Laura Chyntia Bella; Muhammad Zidan (INDO PUBLISHING, 2026)
Marine pollution caused by coal waste is a serious problem for fishermen because it directly impacts the fisheries sector. Contaminants from this waste enter coastal ecosystems, whether dissolved in water, deposited in sediments, or accumulated in marine organisms such as fish, shrimp, shellfish, and seaweed. This situation threatens the balance of the ecosystem as well as the sustainability of fishery resources. The coal spill incident in Meureubo, West Aceh, indicates negligence in industrial waste management and weak enforcement of environmental laws. This study aims to examine these issues from a maritime law perspective, referencing Government Regulation No. 22 of 2021 and the London Convention, and to analyze their impact on fisheries sustainability. The method used is a normative legal approach employing statutory analysis and case studies. The research findings indicate that the pollution in West Aceh has caused significant ecological and economic losses for the fishing community. Furthermore, this incident reflects the suboptimal implementation of law enforcement in the field of environmental protection. Therefore, regulatory reforms, improved oversight effectiveness, and strengthened law enforcement are necessary to prevent similar pollution and ensure the long-term sustainability of fishery resources.